2014
DOI: 10.1021/ar5000727
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Calculations of Electronic Excitations and Relative Hyperpolarizabilities of Electrooptic Chromophores

Abstract: CONSPECTUS: Organic glasses containing chromophores with large first hyperpolarizabilities (β) are promising for compact, high-bandwidth, and energy-efficient electro-optic devices. Systematic optimization of device performance requires development of materials with high acentric order and enhanced hyperpolarizability at operating wavelengths. One essential component of the design process is the accurate calculation of optical transition frequencies and hyperpolarizability. These properties can be computed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
94
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(106 citation statements)
references
References 67 publications
(151 reference statements)
12
94
0
Order By: Relevance
“…49,[95][96][97][98] Also, the resulting non-empirically optimized parameters in our calculations are close to those obtained using other LC functionals with good performance for a variety of properties. 49,[95][96][97][98] Also, the resulting non-empirically optimized parameters in our calculations are close to those obtained using other LC functionals with good performance for a variety of properties.…”
Section: Resultssupporting
confidence: 70%
“…49,[95][96][97][98] Also, the resulting non-empirically optimized parameters in our calculations are close to those obtained using other LC functionals with good performance for a variety of properties. 49,[95][96][97][98] Also, the resulting non-empirically optimized parameters in our calculations are close to those obtained using other LC functionals with good performance for a variety of properties.…”
Section: Resultssupporting
confidence: 70%
“…In at horoughs tudy on electro-optic chromophores with functionals of varying degrees of HF exchange, Johnson et al [59] concluded that the relationship between the percentage of long-range HF exchange and both b (determined from experimental hyper-Rayleigh scattering) and l max is nearly linear,atrend similar to that reported in our study.A lthough none of the DFT methods examined by Johnson et al offers small errors both in electronic excitations and hyperpolarisability,M 06-2X and CAM-B3LYP came across as ag ood compromise.…”
Section: Calculatedmacroscopic Nlo Propertiessupporting
confidence: 88%
“…At present the number of works dealing with the calculations of molecular polarizabilities of stacked clusters is essentially fewer than those where the energy of binding π–π interactions is studied. As a rule the choice of an adequate computational level was done by the example of isolated chromophores . To select the calculation method to be used for reliable NLO characteristics estimation for both isolated chromophores and stacked clusters, it is necessary to come to an agreement on the reference data.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional DFs, such as B3LYP or PBE0 ones, assumed to provide reliable geometry and physical characteristics of separate chromophores, are inadequate in the case of clusters where intermolecular interactions play the determining role, since these DFs do not account for long‐range dispersion interactions . Studying the geometry and static molecular polarizabilities of separate DR, we have examined range‐separated (RS) DFs ωB97X and CAM‐B3LYP .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation